Work and family in the eWork era - Cullen, Kevin (IOS Press ; Ohmsha, 2003)
This work studies the effects of trends in work organizations in the Information Society on the work-family balance. It presents the results of a study of these developments in four European countries - Ireland, Germany, Denmark, and Italy - representing four quite different cultural contexts.